Analisis Strategi Influencer Marketing Joybasic.Id Dalam Meningkatkan Brand Awareness di Tiktok - Fifian; Anang Muftiadi; Mas Rasmini (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2025)
Social media has become an integral part of digital marketing strategies, especially in the fashion industry, which is highly visual and trend-driven. TikTok, as a short-form video platform, offers substantial opportunities through influencer marketing strategies that can rapidly and broadly build brand awareness. This study analyzes the influencer marketing strategy employed by the local fashion brand Joybasic in shaping brand awareness via TikTok. The central problem examined is how elements within influencer content such as visual storytelling, personal narratives, and consistent aesthetics contribute to audience perception of the brand. This research uses a descriptive qualitative approach with a case study method focused on Joybasic's campaigns featuring TikTok influencers @curatedmess_ and @kharisjournal, supported by digital documentation, audience engagement data, and content observation. The findings reveal that strategic influencer selection aligned with brand identity, combined with consistent narrative and visual storytelling, creates emotional engagement and strengthens brand associations. Authentic narratives and minimalist visual approaches positively impact perceived product quality and consumer trust. Furthermore, audience engagement increases through interactive and participatory formats tailored to TikTok’s algorithm. The study concludes that strategically integrated influencer marketing, when aligned with brand values and image, significantly enhances brand awareness, particularly among Gen Z users. It recommends the use of authentic narratives and credible influencers as essential components for building brand perception in the digital fashion landscape.